2000
DOI: 10.1103/physreve.61.1170
|View full text |Cite
|
Sign up to set email alerts
|

Resonances while surmounting a fluctuating barrier

Abstract: Electronic analog experiments on escape over a fluctuating potential barrier are performed for the case when the fluctuations are caused by Ornstein-Uhlenbeck noise (OUN). In its dependence on the relation between the two OUN parameters (the correlation time tau and noise strength Q) the nonmonotonic variation of the mean escape time T as a function of tau can exhibit either a minimum (resonant activation), or a maximum (inhibition of activation), or both these effects. The possible resonant nature of these fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The effect is due to higher probabilities of the extreme events (large fluctuations) allowed by the Lévy statistics. Similarly to the Gaussian-bath case, a typical asymptotic behavior of the MFPT has been recovered for large and small frequencies of the dichotomous noise: for small γ MFPT tends to the average MFPTs for the both barrier configurations, while for large γ it becomes equal to the MFPT over the average potential barrier [29,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect is due to higher probabilities of the extreme events (large fluctuations) allowed by the Lévy statistics. Similarly to the Gaussian-bath case, a typical asymptotic behavior of the MFPT has been recovered for large and small frequencies of the dichotomous noise: for small γ MFPT tends to the average MFPTs for the both barrier configurations, while for large γ it becomes equal to the MFPT over the average potential barrier [29,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…2 (lower panel). By comparison to the results obtained for a motion of a particle subject to the additive white Gaussian noise [29,30,31,32,33], the value of the MFPT is smaller and resonant activation is observed at lower frequencies γ. Moreover, for H ± = ±8, asymptotic values of MFPT estimated for γ → ∞ and γ → 0 are higher (lower) than in the corresponding white Gaussian noise case [29,30,33].…”
Section: Stochastic Differential Equations With Stable Noisesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 For the classical case, in particular for systems in which a classical particle interacts with a time-dependent potential, different formalisms were developed, including treatments of the problem of a time-modulated barrier 5,21,22 and of a classical particle in a time-dependent oscillating well. 23,24 Consideration of the dynamics of these problems in the presence of noise has recently led to exact descriptions of diffusion within static single and double-square well potentials, 25,26 the introduction of an external field for twolevel systems in a classical potential, 27 a general solution of the problem of activated escape in periodically driven systems, 28 analytic solutions for the problem of a piecewise bistable potential in the limit of weak external perturbation, 29 calculation of the escape flux from a multiwell metastable potential at times preceding the formation of quasiequilibrium, 30 activation over a randomly fluctuating barrier, 31,32 and diffusion across a randomly fluctuating barrier. 33 In this paper we revisit the problem of a classical particle interacting with an infinitely deep potential well containing a periodically oscillating square well, with the aim of describing some of its scaling properties.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this study lies in our interest in noise-induced resonance-like phenomena, a subject that has been extensively investigated by physicists for some twenty years. It was found that under some conditions, potential fluctuations can lead to resonant activation [5][6][7], an effect in which the mean time to overcome a potential barrier may significantly decrease, provided the barrier height changes randomly with a characteristic time scale of the same order as the characteristic time scale t r of the intrawell processes [8]. Although resonant activation is investigated mostly as a generalization of the standard Kramers' problem [9] of Brownian diffusion, its simplest presentation by means of a discrete kinetic scheme is possible [6,10].…”
Section: Introductionmentioning
confidence: 99%